The data. - Upson, S. (IEEE spectrum)
This article discusses about the installation of solar cells on the roof, that will help the country to get a grip on global warming and stop depending on foreign fossil supplies. The attractiveness of renewable technologies depends not only on their energy paybacks. But too often, energy technologies are discussed solely in terms of their direct cost to end users without taking into account surrounding factors.